How Assessment Centres Help Organisations to Select Suitable Applicants?- A Qualitative Study Based on UK Organisations from the Perspective of Job Applicants - Jin, Guoxing (2020)
Assessment centres (ACs) are popular and effective personnel selection processes that are adopted by public as well as private organisations for selection and promotion, as well as development purposes. This qualitative research is conducted to investigate the utility of AC exercises and how these exercises help organisation select the suitable candidates. For this, data was collected through semi-structured interviews with eleven job applicants who participated in an AC in the UK public or private sectors recent 5 years. A lot of exercises that are based on what these eleven job applicants experienced during ACs would be discussed in detail. The present study illustrated how these exercises come into effect and help applicants predict their actual job environment. This work also highlighted that the applicant perceptions in ACs is directly related to their later intentions.